2017
DOI: 10.1177/0022034517691757
|View full text |Cite
|
Sign up to set email alerts
|

Proanthocyanidins-Loaded Nanoparticles Enhance Dentin Degradation Resistance

Abstract: Previous studies reported that grapeseed extract (GSE), which is rich in proanthocyanidins (PAs), improves the biodegradation resistance of demineralized dentin. This study aimed to investigate the effect of a new GSE delivery strategy to demineralized dentin through loading into biodegradable polymer poly-[lactic-co-glycolic acid] (PLGA) nanoparticles on the biodegradation resistance in terms of structural stability and surface/bulk mechanical and biochemical properties with storage time in collagenase-contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 39 publications
2
21
0
2
Order By: Relevance
“…3c). In this study the hardness values of normal dentin were in good agreement with the previous studies of dentin [32,33]. And in our studies, the element P in DGI-dentine shown a lower level compared with normal dentine, which verify the positive association between dentin hardness and mineral content [34,35].…”
Section: Discussionsupporting
confidence: 91%
“…3c). In this study the hardness values of normal dentin were in good agreement with the previous studies of dentin [32,33]. And in our studies, the element P in DGI-dentine shown a lower level compared with normal dentine, which verify the positive association between dentin hardness and mineral content [34,35].…”
Section: Discussionsupporting
confidence: 91%
“…First, the dentine hardness and collagen elasticity in the proband were significantly lower than in the control samples ( p < 0.05), which was consistent with the clinical high brittleness phenomenon (Seyedmahmoud et al, 2017 ). Meanwhile, the hardness values of the control dentine were in good agreement with the results of previous studies on dentine (Fawzy et al, 2017 ; Yi et al, 2020 ). Second, the level of in dentine of patients with DGI-I patient was shown to be lower compared with that in normal dentine, which may have influenced the dentine hardness and mineral content (Park et al, 2020 ).…”
Section: Discussionsupporting
confidence: 90%
“…radical scavenger, almost without side effects [28,29,32,33]. It was applied successfully in many dental treatments.…”
Section: Antioxidant Group Versus Non-antioxidant Groupmentioning
confidence: 99%
“…In order to prevent the delay of recovery treatment after bleaching, various antioxidant agents, including sodium ascorbate (SA) [16,21,27], proanthocyanidins (PC) [28,29], green tea extract [4,5,7,13,16], pine bark extract [30], aloe extract [5,16], and grape seed extract [16,31], have been attempted, among which, SA and PC have shown promising results [4,5,14,28,29]. Nevertheless, the results of antioxidants with different types and durations are quite different [4,5,[8][9][10]32,33]. Consequently, we conducted the present in vitro study to compare the effects of 10% SA and 5% PC on the immediate BS-RBE.…”
Section: Introductionmentioning
confidence: 99%